High Flow Spontaneous AV Fistula Occurring between Middle Cerebral Artery and Sagittal Sinus - Yildirim, Gokhan; Ergün, Ahmet; Kaplan, Metin (Wolters Kluwer Medknow Publications, 2023)
[Abstract Not Available]
Keywords: Arteriovenous Fistula; Cerebral Angiography; Cranial Sinuses; Humans; Middle Cerebral Artery; arteriovenous fistula; blood flow; brain radiography; case report; child; clinical article; clinical feature; computed tomographic angiography; convulsion; faintness; human; Letter; magnetic resonance venography; male; middle cerebral artery; neurologic examination; preoperative evaluation; preschool child; superior sagittal sinus; x-ray computed tomography; arteriovenous fistula; brain angiography; complication; cranial sinus; diagnostic imaging